Influence of supervision ratio on functional physical performance and cellular health to collective multicomponent training in untrained adults aged - Ewertton de Souza Bezerra; Andreza dos Santos Silva; Jéssica Naveca De Abreu; Rômulo de Oliveira Sena; Luis Mochizuki (Archives of Gerontology and Geriatrics Plus, 2024)
In pragmatic settings, involving elderly individuals in physical activity programs typically does not require individualized training. Thus, the aim of this study was to assess the impact on functional physical performance and cellular health resulting from a high (10 participants to 1 supervisor) versus low (20 participants to 1 supervisor) supervision ratio in a group-based multicomponent training program for older women. The experimental procedure presented three phases: a) pre-assessment (physical functional performance and cellular health); b) multicomponent training program (2 sessions/week); c) post-assessment. Performance variables were normalized with a t-score and the statistical analysis was based on the individual relative position in the t-score. After the collective multicomponent training intervention, 55 % of participants were above the mean t-score; however, low supervision ratio group (20:1) did not change functional physical performance and cellular health. A high supervision ratio is an important condition to improve individual older women response during a collective multicomponent training program.